One Day of #Feminism: Twitter as a Complex Digital Arena for Wielding, Shielding, and Trolling talk on Feminism. (4th May 2019) - Lopez, Kimberly J.; Muldoon, Meghan L.; McKeown, Janet K. L.
ABSTRACT: This article offers a critical analysis of the uses of the hashtag '#feminism' on Twitter. To do so, we collected all English-language tweets shared publicly and containing the #feminism on Twitter in one 24-hour period and analyzed the content of those tweets. We found tweets with #feminism content served to (1) discuss understandings of feminism(s), (2) describe perceptions of feminists, (3) respond to/promote misogyny, and (4) express perceived relevance of feminism as a social movement. Beyond describing how #feminism is used in Twitter tweets, our findings inform our presentation of the use of #feminism to wield, shield, and troll feeds on feminism. We also discuss the opportunities for Twitter, as a digital leisure space, to be used to examine more closely complex, ongoing, and evolving conversations about feminism.